Pengaruh Potongan Margin (Muqashah Ar-Ribhi) Terhadap Minat nasabah dalam Memanfaatkan Pembiayaan Murabahah di Bank Pembiayaan Rakyat Syariah (BPRS) Bhakti Sumekar (Studi Kasus di Kantor Cabang Bluto Sumenep) - Hotimatul Adalah; Fadllan Fadllan (Institut Agama Islam Negeri Madura, 2016)
PT. BPRS Bhakti Sumekar Branch Bluto Sumenep is one of Bank Syari’ah Financing which functions as an intermediary that has its own the market in distributing financial products, namely the public and small businesses that need capital but in analyzing the customer worthy or not to be given financig by using the ratings analysis 5C to anticipate the risk of financing as doubted, less smooth and credit jammed. This type of research used in this research is quantitative research using using simple linear regression method where the purpose of simple linear regression is to forecast or predict systematically about what is most likely to happen in the future based on the information of the past and present-have for mistakes can be minimized. The data used are primary data obtained through questionnaires. Sample of 73 customers. The instruments used in data collection is by using the questionnaire method, documentation and interviews. While proving the hypothesis using a calculation by the classical assumption test, t test and f test. The results of this research using simple linear regression analysis which states that there is influence between margin pieces (muqashah ar-Ribhi), the equation Y = 19.060 + 0.345 X. Based on the results of testing the hypothesis with t test and F test shows significant value where t count> t table = 6.784 0.000 ˃1.666 with significant level of 0,000 less than 0.05. And the F test showed the value of Fcount ˃ Ftabel (46.027 ˃ 3.98) with the level of sig. Of as big as 0000. It can be concluded that simultaneously margin pieces (muqashah ar-Ribhi) has a significant effect on the customers' interest in utilizing financing murabaha at Bank Financing Shari’ah People (BPRS) Bhakti Sumekar (Case Study at the Branch Office Bluto Sumenep).